Estudo de caso de uma criança com características de altas habilidades: problematizando questões referentes à inclusão escolar - Rech, Andréia Jaqueline Devalle (2007)
The present research inserts itself in the Research Line of Special Education of the Course of Mastership of the Program of Post-Graduation in Education of the Federal University of Santa Maria UFSM. The interest of doing this research came from the moment that a female student with gifted and talented features was led to the project PIT team to proceed a pedagogical evaluation. This evaluation had the aim of verifying if this student could achieve the pedagogical conditions to enter in the first grade of the elementary school precociously. After the conclusion of the pedagogical evaluation it was realized that the student was pedagogically able to enter the school. From this fact, we investigated the process of school inclusion of the student with gifted and talented features, who attended the first grade of elementary school in a state public school in Santa Maria RS, problematizing questions related to school inclusion. Besides, other questions guided this study, among them: to accomplish a survey of the gifted and talented features this student showed during the observations in the classroom and on the family environment; to investigate in what way the disciplinary devices were used by the teacher A to become efficient the action of disciplinary power over the students bodies , especially on the observed student; to verify how the normative practices act around of the gifted and talented students; to analyze the speeches produced by the school inclusion polities; to propose a discussion about the school inclusion of the gifted and talented students hoping to problematize it. To answer these questions, I have made use of some Foucault s references besides other researchers who study this area. The data were collected from the observation of the daily routine in the classroom that the student was registered, as well as enrichment school activities, besides interviews with the student s teacher and parents. The results of the research point to a pedagogical practice that the disciplinary power and the power of the rule (FOUCAULT, 1988) contributed to the female student with gifted and talented features, in spite of being included, also was exposed to school exclusion situations.